Dynamic Interplay of Host and Pathogens in an Avian Whole-Blood Model - Sreekantapuram, Sravya; Lehnert, Teresa; Prauße, Maria T. E.; Berndt, Angela; Berens, Christian; Figge, Marc Thilo; Jacobsen, Ilse D. (Frontiers in Immunology, 2020)
Microbial survival in blood is an essential step in the development of disseminated diseases and blood stream infections. For poultry, however, little is known about the interactions of host cells and pathogens in blood. We established an ex vivo chicken whole blood infection assay as a tool to analyze interactions between host cells and three model pathogens, Escherichia coli, Staphylococcus aureus, and Candida albicans. Following a systems biology approach, we complemented the experimental measurements with functional and quantitative immune characteristics by virtual infection modeling. All three pathogens were killed in whole blood, but to a different extent and with different kinetics. Monocytes, and to a lesser extent heterophils, associated with pathogens. Both association with host cells and transcriptional activation of genes encoding immune-associated functions differed depending on the both the pathogen and the genetic background of the chickens. Our results provide first insights into the quantitative interaction of three model pathogens with different immune cell populations in avian blood, demonstrating a broad spectrum of different characteristics during the immune response that depends on the pathogen and the chicken line.